2020
DOI: 10.1016/j.healun.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in heart transplantation during COVID-19: A single-center experience

Abstract: BACKGROUND: Orthotopic heart transplantation (OHT) recipients may be particularly vulnerable to coronavirus disease 2019 (COVID-19). OHT during the pandemic presents unique challenges in terms of feasibility and safety. METHODS: Chart review was performed for consecutive OHT recipients with COVID-19 and waitlisted patients who underwent OHT from March 1, 2020 to May 15, 2020. RESULTS: Of the approximately 400 OHT recipients followed at our institution, 22 acquired COVID-19. Clinical characteristics included me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 18 publications
(20 reference statements)
5
41
1
3
Order By: Relevance
“…Future studies are needed to understand the impact of telemonitoring on long-term care and outcomes for this population. Among patients with severe HF, weighing the risk of exposure to COVID-19 against the benefit of life-saving therapies, such as mechanical circulatory support and heart transplantation, is particularly relevant and must be carefully considered on a case-by-case basis ( 39 ). Finally, understanding the mechanisms that underlie the high risk of complications and mortality among patients with HF begs the question of whether specific therapies to combat acute infection in COVID-19 should be used based on the history of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed to understand the impact of telemonitoring on long-term care and outcomes for this population. Among patients with severe HF, weighing the risk of exposure to COVID-19 against the benefit of life-saving therapies, such as mechanical circulatory support and heart transplantation, is particularly relevant and must be carefully considered on a case-by-case basis ( 39 ). Finally, understanding the mechanisms that underlie the high risk of complications and mortality among patients with HF begs the question of whether specific therapies to combat acute infection in COVID-19 should be used based on the history of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Since these initial reports, other papers describing the clinical course of COVID-19 in HTR have been published from Germany and the United States. They also featured HTR who were remote from transplant and were mostly receiving relatively low-dose maintenance immunosuppression [ 2 , 4 , 5 , 7 – 9 ]. Recently, Latif et al described a single-center case series of 28 HTR with a confirmed diagnosis of COVID-19 in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…Singhvi et al also described a single -center case series of 22 HTR in the disease epicenter in New York. The median time from HT was 4.6 years, and the overall mortality was 22.7%, reaching 26.3% in hospitalized patients [ 9 ]. Finally, Rivinius et al reported 21 HTR with COVID-19 in a recent nation-wide survey of all HT centers in Germany during the first months of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that the risk of COVID-19 infection in heart transplant recipients is not higher than the general population if proper precautions are taken. 52 Since few studies have been done in this population, the differences in symptoms, laboratory tests, and radiographic features have not been determined. 53 Also, solid organ transplantation (SOT) recipients such as heart transplant recipients are at greater risk of COVID-19 because of their potential anti-rejection immunosuppressive regimens.…”
Section: Covid-19 and Heart Transplant (Ht)mentioning
confidence: 99%